Initial rhythm and survival in refractory out-of-hospital cardiac arrest. Post-hoc analysis of the Prague OHCA randomized trial. (December 2022) - Havranek, Stepan; Fingrova, Zdenka; Rob, Daniel; Smalcova, Jana; Kavalkova, Petra; Franek, Ondrej; Smid, Ondrej; Huptych, Michal; Dusik, Milan; Linhart, Ales; Belohlavek, Jan
Abstract: Background: The prognosis of refractory out-of-hospital cardiac arrest (OHCA) is generally poor. A recent Prague OHCA study has demonstrated that an invasive approach (including extracorporeal cardiopulmonary resuscitation, ECPR) is a feasible and effective treatment strategy in refractory OHCA. Here we present a post-hoc analysis of the role of initial rhythm on patient outcomes. Methods: The study enrolled patients who had a witnessed OHCA of presumed cardiac cause without early recovery of spontaneous circulation. The initial rhythm was classified as either a shockable or a non-shockable rhythm. The primary outcome was a composite of 180 day-survival with Cerebral Performance in Category 1 or 2. Results: 256 (median age 58y, 17% females) patients were enrolled. The median (IQR) duration of resuscitation was 52 (33–68) minutes. 156 (61%) and 100 (39%) of patients manifested a shockable and non-shockable rhythm, respectively. The primary outcome was achieved in 63 (40%) patients with a shockable rhythm and in 5 (5%) patients with a non-shockable rhythm (p < 0.001). When patients were analyzed separately based on whether the treatment was invasive (n = 124) or standard (n = 132), the difference in the primary endpoint between shockable and non-shockable initial rhythms remained significant (35/72 (49%) vs 4/52 (8%) in the invasive arm and 28/84 (33%) vs 1/48 (2%) in the standard arm; p < 0.001). Conclusion: An initial shockable rhythm and treatment with an invasive approach is associated with a reasonable neurologically favorable survival for 180 days despite refractory OHCA. Non-shockable initial rhythms bear a poor prognosis in refractory OHCA even when ECPR is readily available.